Structure of the human alpha 2 subunit gene of the glycine receptor--use of vectorette and Alu-exon PCR. - Monani, U; Burghes, A H (Genome Research, 1996)
The alpha subunit of the glycine receptor is encoded by multiple genes that display developmental and tissue-specific expression. The alpha 1 subunit gene is expressed predominantly in the adult brain stem and spinal cord, whereas the alpha 2 subunit gene is expressed in fetal brain and spinal cord. We wished to determine the genomic organization of the human alpha 2 subunit gene as well as to define the 5' ends of the alpha 1 and alpha 2 subunit genes. Gene structure can be defined rapidly from yeast artificial chromosome (YAC) DNA sources by the use of vectorette-exon polymerase chain reaction (PCR). However, YACs frequently contain small deletions that complicate the determination of the complete exon-intron structure of a gene, and this often necessitates the isolation of additional clones. In this study we have used vectorette-exon PCR from YAC DNA to define exons of the glycine receptor alpha 2 subunit gene. To define those exons that were absent in the isolated YACs, we used Alu-exon PCR on genomic DNA, using nested primers to obtain specificity in the PCR reactions. The alpha 2 subunit gene was found to contain nine exons varying in size from 68 bp (exons 3A and 3B) to 581 bp (exon l). All of the intron-exon boundary sequences conform to consensus splice donor and acceptor sites. In addition, we have defined the 5' end of this gene as well as that of the alpha 1 subunit gene by RACE-PCR. The structures of the alpha subunit glycine receptor genes in humans are very similar to each other and to the alpha subunit genes in mice.